Scoping review of knowledge and attitude of high school sports players to concussion - Jankelowitz, S.; Tastula, K. (American Journal of Sports Science, 2026)
Sports related concussion has received a lot of media and scientific attention because of the risk of longterm or delayed cognitive changes. These include the pathological changes consistent with chronic traumatic encephalopathy and the clinical condition defined as traumatic encephalopathy syndrome. While there have been major changes to concussion management in professional sports, little is known about knowledge and attitudes with respect to concussion in high school athletes. This scoping review assessed the currently available data over the last 25 years. The authors identified only 6 studies that explored the knowledge and attitudes of the athletes themselves. Most paper were concerned with coach or parent related knowledge and beliefs. The data was mostly related to male rugby players and showed better knowledge in metropolitan versus rural areas in most studies. Of note, the school nurse was highlighted as a previously not considered source of advice with respect to concussion management. This was particularly so in rural areas or low socioeconomic areas where access to a doctor was more difficult. The studies also highlighted that despite the improved knowledge with respect to concussion, there has not been an associated change in behaviour with most high school athletes continuing to play, or returning to play early, for so called `important" matches.